Analysis of Voids and Porosity and Its Influence on The Quality of Syntactic Foam Composites - Munawar, Maulana Dzaki; Hakim, Moh Luqman; Wijaya, Ade Mundari; Novriadi, Dwi (Universitas Negeri Semarang, 2023)
The syntactic foam composite possesses both light and strong qualities. Syntactic foam composite is commonly employed as a buoyant lighting material in amphibious aircraft due to its excellent foaming capability. Composite syntactic foam is utilized because of its ability to efficiently support material drying while maintaining excellent structural strength (mechanical characteristics). In order to ascertain the syntactic compound density, one can determine the composite density based on the ASTM D790 standard. This involves evaluating the porosity calculation and doing a literature review to establish the characteristics of the void. The density of a syntactic foam composite is determined by the density of the filling matrix (microballoon k15), the percentage of porosity, and the identification of voids. The use of the K15 microballoon material will reduce the overall density of the composite because of its substantial structure. The number of small cavities within the composite syntactic foam is indicated by the porosity ratio.Nevertheless, not all apertures present in syntactic foam composites can be classified as k15 microballoon structures, as the composite manufacturing process may result in the formation of air bubbles that become trapped within the composite. The function has no return value. The excessive presence of voids can significantly reduce the density and mechanical strength, leading to a drop in the overall quality of the syntactic foam composite. Porosity analysis is crucial for assessing the quality of drying in syntactic foam composites. The study involved assessing the composite density of syntactic foam with varying concentrations of 0-50% w/w of the k15 microballoon material, following the ASTM D790 standard. The porosity value of the foam was subsequently determined and studied. The findings of this study can serve as a robust point of reference for analyzing the correlation between the density of the reference material and the composite syntactical foam's relative density in different variations.